2021
DOI: 10.1097/md.0000000000027442
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6 as a novel risk biomarker of fractured ankles

Abstract: Ankle fractures are the most common intra-articular fractures. Osteoporosis is a common and frequent disease among the elderly with a poor prognosis and high risk of fractured ankles. However, the relationship between vitamin B6 and the incidence of fractured ankles in patients with osteoporosis is unclear. A total of 101 patients with osteoporosis were recruited. Clinical and followed-up information was recorded. And the vitamin B6, albumin, globulin, and hemoglobin in the blood were tested. Pearso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Vitamin B6 is necessary for the cross-linking of lysine oxidase collagen, which plays an important role in maintaining bone mass. Meanwhile, vitamin B6 de ciency reduces the concentration of cross-linking intermediates and disrupts collagen cross-linking in bone [37]. Enrichment of L-lysine has previously been observed in osteopenia [38].This supports the upregulation of L-methylphenidate involved in lysine degradation in plasma differentials.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Vitamin B6 is necessary for the cross-linking of lysine oxidase collagen, which plays an important role in maintaining bone mass. Meanwhile, vitamin B6 de ciency reduces the concentration of cross-linking intermediates and disrupts collagen cross-linking in bone [37]. Enrichment of L-lysine has previously been observed in osteopenia [38].This supports the upregulation of L-methylphenidate involved in lysine degradation in plasma differentials.…”
Section: Discussionsupporting
confidence: 65%
“…Estrogen is one of the main hormones regulating bone metabolism [36]. Estrogen de ciency affects bone cell-mediated remodeling, reducing bone mass and damaging bone microstructure [37]. Vitamin B6 de ciency may also be a risk factor for bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…The other study has also demonstrated that they are positively associated with a fractured ankle. 40 Therefore, vitamin B6 intake is potentially related to bone health, and adults need to consume foods rich in vitamin B6. Vitamin B6-rich foods are beef liver, tuna, salmon, chicken breast, chickpeas, bananas, cottage cheese, nuts, and onion.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the normally-fed rats’ plasma testosterone levels were significantly higher than those in the other three groups, the decrease of testosterone low calcium for a long time, Recovery may not be achieved by calcium supplementation and the addition of chondroitin sulfate [ 57 ]. Estrogen deficiency affects bone cell-mediated remodeling, reducing bone mass and damaging bone microstructure [ 58 ]. Microbiota play a significant role in lipid homeostasis by fermenting dietary fiber for production.…”
Section: Discussionmentioning
confidence: 99%